Duodenal microbiome changes in postmenopausal women: effects of hormone therapy and implications for cardiovascular risk. Issue 3 (24th March 2022) - Leite, Gabriela; Barlow, Gillian M.; Parodi, Gonzalo; Pimentel, Maya L.; Chang, Christine; Hosseini, Ava; Wang, Jiajing; Pimentel, Mark; Mathur, Ruchi
Abstract: Objective: Hormone therapy (HT) is used to treat menopause-related conditions and symptoms. The small intestine plays key roles in metabolic and endocrine function, but the effects of HT on the small intestinal microbiome are unknown. Here, we characterize duodenal microbiome differences, and the effects of HT, in postmenopausal women. Methods: Female participants undergoing esophagogastroduodenoscopy who were postmenopausal and taking HT (HT+), postmenopausal but not taking HT (HT−), or of reproductive age and not taking exogenous hormones (RA), were identified and matched for body mass index (±3 kg/m 2 ). DNAs were isolated from duodenal aspirates obtained during upper endoscopy. V3 and V4 libraries were used for 16S rRNA sequencing. Serum hormone levels were analyzed by Luminex FlexMap. Results: The core duodenal microbiome was different in HT− participants ( n  = 12) when compared with RA participants ( n  = 10), but more similar in HT+ ( n  = 13) and RA participants. HT− participants had increased Proteobacteria taxa, leading to greater microbial dysbiosis compared with HT+ participants, and had decreased prevalence of Bacteroidetes, which was associated with higher fasting glucose levels, lower duodenal microbial diversity, and lower testosterone levels. HT+ participants had significantly higher estradiol ( P  = 0.04) and progesterone ( P  = 0.04), and lower fasting glucose ( P  = 0.03), than HT− participants, and had increased relative abundance of Prevotella ( P  = 0.01), and decreased Escherichia ( P  = 1.12E-7), Klebsiella ( P  = 5.93E-7), and Lactobacillus ( P  = 0.02), all associated with lower cardiovascular disease risks. Conclusions: These findings support previous studies suggesting that HT may have beneficial effects following menopause, and although preliminary, may also support a beneficial effect of HT on the duodenal microbiome.